Human Resource Empowerment at Madrasah Aliyah Negeri 3 Kota Jambi - Maisah Maisah; Husin Husin; Fadlilah Fadlilah (Universitas Muhammadiyah Enrekang, 2024)
This research explores the human resource empowerment strategy at Madrasah Aliyah Negeri (MAN) 3 Kota Jambi, focusing on the efforts made to enhance the competencies of teachers and staff through training and professional development programs. The study reveals that the leadership at MAN 3 Kota Jambi has adopted a holistic approach to human resource empowerment, incorporating workshops, seminars, and skill-building activities to improve teaching quality. Additionally, the creation of a collaborative and supportive work environment and the recognition of teachers' performance are key components of the strategy. Despite challenges such as limited resources, varying skill levels among teachers, resistance to change, and time constraints, the empowerment efforts have led to significant improvements in educational quality. The research highlights the positive impact of these efforts on student learning outcomes, teacher motivation, and the overall reputation of the madrasah. However, overcoming existing challenges is essential for achieving long-term success in human resource development at the institution